Analisis Deskriptif Biaya Produksi dan Laba Bersih pada PT Ultrajaya Milk Industry Tbk Periode 2018–2025: Descriptive Analysis of Production Costs and Net Profit at PT Ultrajaya Milk Industry Tbk for the Period 2018–2025 - Meysha Van Heving; Cut Sabina Ayuni; Angela Stevi Syakira; Nadila Yosep Mareta; Sarip Hidayatuwloh (PT Cakrawarti Empat Proksi, 2026)
This study aims to analyze the effect of production costs on net profit at PT Ultrajaya Milk Industry Tbk during the period 2018–2025. The background of this research is based on the importance of controlling production costs in the food and beverage industry to maintain profitability in the midst of increasingly fierce market competition. The research method used is qualitative descriptive by utilizing secondary data in the form of the company's annual financial statements for the period 2018–2025 published through the Indonesia Stock Exchange. Data analysis techniques are carried out through document review, descriptive interpretation of cost and profit trends, and comparative studies between periods to understand the patterns of intervariable relationships in depth. The results of the study show that there is a tendency that changes in production costs are followed by changes in the company's net profit. When production costs can be managed more efficiently, net profit tends to increase. In contrast, the increase in production costs that is not offset by revenue growth is related to a decline in profit margins.